Unmasking the rock art of Chivi area in Masvingo province - Mubaiwa, Fitzroy (Midlands State University, 2018)
Rock art studies have always been a key source of information to archaeologists in a bid to reconstruct past life societal practices. Most scholars argue that the execution of rock art was a means of documenting the social, economic and political activities. Studying rock art sites therefore provide a detailed insight in to the activities that were done by prehistoric communities at a global view. In order to understand the meaning behind rock art, one has to first of all document the rock art motifs so as to better analyse the depicted motifs. Documentation of rock art sites in Zimbabwe has been focused on the already known rather than searching for new sites that can provide more information. This research gap was covered by the identification of new rock art sites in Chivi area in Masvingo. The objectives of the study which were to locate, document, characterize and assess the condition of rock art sites was achieved by adopting the descriptive research design which acted as the bridge between the research questions and the results. A total number of 3 sites were located namely Charimira, Sedza and Madya. The documentation of sites was done making use of photography as well as G.P.S coordinates for mapping of the area. Characterisation of the motifs identified within the panels was done with aspects as style, association and pigment analysis being achieved. The rock art sites are well preserved though little needs to be done with regards to graffiti as it is a human induced factor. The overall aim of the study was therefore achieved as 3 rock art sites were located and documented adding new information to the already available rock art sites in Zimbabwe.